2012
DOI: 10.3109/08820139.2012.723769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of High-Mobility Group Box 1 Protein Concentration in Serum of Patients withM. tuberculosisInfection

Abstract: Infection with Mycobacterium tuberculosis is accompanied by an intense inflammatory response. Recently, a new mediator of inflammation, HMGB1 protein has been identified that contributes to acute lung injury. However, its role in the systemic inflammatory response in tuberculosis has not been thoroughly investigated. We investigated the systemic levels of HMGB1 and TNF-α in patients with active and latent lung tuberculosis as a prognostic marker of disease activity. The study was performed to 70 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In previous reports, HMGB1 level was significantly increased in patients with TB compared with HC (TB patients vs. HC, 47.5±26.1 ng/mL vs. 13.8±7.3 ng/mL; roughly 2.2 ng/mL vs. 1.3 ng/mL [mean values not shown], respectively)1112. There was a large difference between the HMGB1 levels between the two studies.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In previous reports, HMGB1 level was significantly increased in patients with TB compared with HC (TB patients vs. HC, 47.5±26.1 ng/mL vs. 13.8±7.3 ng/mL; roughly 2.2 ng/mL vs. 1.3 ng/mL [mean values not shown], respectively)1112. There was a large difference between the HMGB1 levels between the two studies.…”
Section: Discussionmentioning
confidence: 79%
“…Several studies have described the roles of HMGB1 in pathological states, including atherosclerosis, arthritis, acute lung injury, and bacterial pneumonia8910. A few papers have reported that the serum level of HMGB1 was increased in patients with tuberculosis (TB)1112. However, only limited information is currently available about the role of HMGB1 in TB infection.…”
Section: Introductionmentioning
confidence: 99%
“…IL-1β, IL-10, TNF-α) can be challenging; and circulating ‘receptor-bound’ HMGB1 (e.g. bound to soluble RAGE) cannot be measured accurately with the current assays [ 16 , 20 , 25 , 26 ]. As such, gene expressions were also studied.…”
Section: Discussionmentioning
confidence: 99%
“…bovis BCG [ 19 ] can effectively induce secretion of HMGB1, leading to cytokine hyperactivation and lung tissue damage. Recently, increased HMGB1 in serum of MTB-infected patients is reported but its significance is uncertain [ 20 ]. In the current study, we hypothesized that HMGB1/RAGE signaling and the pro-inflammatory cytokine responses play significant roles in pathogenesis and disease manifestations in patients with active pulmonary tuberculosis (PTB).…”
Section: Introductionmentioning
confidence: 99%
“…92 TLR2 also recognizes DAMPs, such as HMGB1 released from necrotic cells, representing a mechanism that regulates apoptosis during M. tuberculosis infection. 33,93,94 TLR4 recognizes the mycobacterial HSP, mitochondrial 50S ribosomal protein, and 38-kDa glycoproptein. [95][96][97][98] TIR domain-containing adaptor-inducing interferon β/MyD88 signaling is responsible for NF-κB activation in response to M. tuberculosis Hsp70-mediated activation of DCs.…”
mentioning
confidence: 99%